Pengaruh Kepemimpinan Agility, Budaya Organisasi Dan Motivasi Terhadap Agilitas Organisasi (Studi Kasus Pada Pengurus BEM Universitas Islam Malang) - Fahrizal, Fahrizal; Wahono, Budi; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine the influence of Agility leadership, organizational culture, and motivation on the organizational agility of BEM Islamic University of Malang (Case Study on BEM of Islamic University of Malang). The variables used in this study are organizational agility variables (the dependent variable), while the independent variables are Agility leadership, organizational culture, and motivation.The results of this study partially concluded that the leadership variables were Agility, organizational culture, and motivation. there is a significant influence on organizational agility and simultaneously concluded that there is a significant influence between Agility leadership, organizational culture, and motivation variables on organizational agility. Keywords: Agility Leadership, Organizational Culture, and Motivation, Organizational Agility